Long-term outcomes of frontline imatinib therapy for chronic myeloid leukemia in China - Cheng, Fang; Yuan, Guolin; Li, Qiang; Cui, Zheng; Li, Weiming (Frontiers in Oncology, 2023)
Background: Imatinib is the first-line therapy recommended for chronic myeloid leukemia (CML) patients in China. We reported a long-term follow-up study of patients on imatinib as first-line treatment for chronic phase (CP) CML to provide an important reference for the actual clinical treatment regimen of CML patients in China. Methods: We evaluated the long-term efficacy, safety, low-dose attempt after years of treatment, and treatment-free remission (TFR) of 237 CML-CP patients receiving first-line imatinib therapy. Results: The median age was 46 years (interquartile range: 33–55). After a median follow-up of 6.5 years, the cumulative complete cytogenetic response, major molecular response (MMR), and MR4.5 rates were 82.6%, 80.4%, and 69.3%, respectively. The 10-year transformation-free, event-free, and failure-free survival rates were 97.3%, 87.2% and 53.5%, respectively. Fifty-two (21.9%) patients with sustained deep molecular response (DMR) were treated with low-dose imatinib after years of imatinib treatment. No significant differences in the 1-year and 2-year molecular relapse-free survival in MMR and MR4 were observed between the standard-dose and low-dose groups. Twenty-eight (11.8%) patients discontinued imatinib, and the median time to maintain DMR before discontinuation was 8.43 years. Thirteen patients (5.5%) remained in TFR for a median of 43.33 months. No patients transformed to accelerate or blast phase or died. No new, late toxicity was observed, and the most frequent grade 3/4 adverse events were neutropenia (9.3%), anemia (7.6%), thrombocytopenia (6.3%), and rash (4.2%). Conclusion: This study confirmed the long-term efficacy and safety of imatinib for treating Chinese CML patients. Additionally, it demonstrated the feasibility of imatinib dose reduction and TFR attempts in patients with sustained stable DMR after years of imatinib treatment in real-life settings.